Kombinasi Buerger Allen Exercise dan Akupresur dalam Menurunkan Kadar Glukosa Darah pada Diabetes Tipe 2 - Lulu Mardiah; Kuswandi, Asep; Aryanti, Dewi; Cahyati, Yanti (Journal of Pubnursing Sciences, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease characterised by elevated blood glucose levels and currently shows an increasing trend in prevalence, both globally and nationally. The management of DM is not only conducted pharmacologically but also through non-pharmacological therapies such as physical exercise and complementary treatments. Buerger Allen Exercise and acupressure are known to lower blood glucose levels by improving blood circulation and increasing insulin sensitivity. Aims:  To determine the effect of the combination of Buerger Allen Exercise and acupressure on blood glucose levels in patients with type 2 DM at a primary healthcare facility in Tasikmalaya City. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. A total of 30 respondents were selected using purposive sampling. Blood glucose levels were measured before and after the intervention. Data were analysed using the Friedman test. Results:  There was a significant decrease in blood sugar levels before and after the combination intervention of Buerger Allen Exercise and acupressure; the average blood sugar level of pretest 1 was 254.00 mg/dL and pretest 2 was 263.50 mg/dL decreasing to 222.00 mg/dL with a significant value of Chi-Square Calculation > Chi Square Table value (42.467 > 5.991) and p-value (0.000 < 0.05). Conclusion: The combination of Buerger Allen Exercise and acupressure has a significant effect on reducing blood sugar levels in type 2 DM patients at a primary healthcare facility in Tasikmalaya City